Problematika Penguasaan Kosakata Bahasa Mandarin Siswa Kelas VII SMP Frater Makassar - Kasriani, Kasriani; Hasmawati, Hasmawati; Adys, Himala Praptami (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2023)
ABSTRACT This research is a qualitative-quantitative research that aims to find out the problems and factors that influence the problems of mastering Chinese vocabulary for class VII students at SMP Frater Makassar. The population in this study were 179 students of class VII SMP Frater Makassar. The sampling technique was carried out using random sampling, so the sample in this study were students of class VII F, totaling 30 students. The research instruments were in the form of interviews, closed questionnaires and open questionnaires. Data were analyzed using percentage techniques. The results showed that the problems in students' mastery of Mandarin vocabulary were that students were novice students who did not know Hanzi and even had difficulty pronouncing it, students acted normally when they received assignments and felt embarrassed to appear in front of the class to memorize Chinese vocabulary, the time allocation for learning Mandarin still not enough. These problems are influenced by two factors, namely internal factors (student discipline), lack of interest in learning and students' self-confidence in learning Mandarin and external factors (teachers, facilities and infrastructure, and family), namely: teachers sometimes use creative learning media in introducing new vocabulary to students; insufficient number of Chinese language textbooks; parents rarely provide motivation to learn Mandarin. As for other external factors, according to the interview data obtained, the school does not yet have a language laboratory.Keywords: Problems, Vocabular